Answer:x=3
Explanation:
Simplifying
8x + -1(6x + -4) = 10
Reorder the terms:
8x + -1(-4 + 6x) = 10
8x + (-4 * -1 + 6x * -1) = 10
8x + (4 + -6x) = 10
Reorder the terms:
4 + 8x + -6x = 10
Combine like terms: 8x + -6x = 2x
4 + 2x = 10
Solving
4 + 2x = 10
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + 2x = 10 + -4
Combine like terms: 4 + -4 = 0
0 + 2x = 10 + -4
2x = 10 + -4
Combine like terms: 10 + -4 = 6
2x = 6
Divide each side by '2'.
x = 3
Simplifying
x = 3